DB2 UDB for z/OS : Design Guidelines for High Performance and Availability - Bruni, Paolo; Becker, Patric; Henderyckx, Jan; Link, Joseph; Steegmans, Bart (IBM Redbooks, 2006)
Conducting business via the Web and remaining open for business 24 hours a day, seven days a week is now commonplace. Customers come in with unexpected workloads through the Web and operate in a self-service fashion with mostly context-sensitive metadata to guide them. The strong requirement is availability. However, even with new Web applications, most of the core business systems considerations still apply, and performance is critical. Technology has been accelerating for mainframe systems. They had become adept at providing business resiliency accommodating strategic software that has been around for the last several decades such as IMS"!, DB2®, and CICS®, and they have also become a host for developing and running Web applications built in Java"!accommodating the latest business requirements. Businesses need to leverage, extend and integrate the strategic assets which represent multi-year investments to support leading edge technology. DB2 for z/OS® has come a long way and provides facilities to exploit the latest hardware and software technologies, accommodating a majority of user requirements. However, special considerations are required to build high performance applications. If you want to achieve high performance or high availability, you must use the design, programming, and operational techniques applicable to DB2. In this IBM Redbooks publication we discuss many of these techniques and provide guidelines for database and application design. We expect the best practices described in this book will help DB2 professionals design high-performance and high-availability applications. Please note that the additional material referenced in the text is not available from IBM